Detection of Ultra-Low Concentration of Methylene Blue by Porous Silicon Photonic Crystals Covered With Siver Nanoparticles as Efficient Sers Substrate - Nguyen, Thuy Van; Vu, Chinh Duc; Pham, Thanh Binh; Pham, Van Hoi; Bui, Huy; Vu, Thi Hong Hanh; Pham, Van Hai (Communications in Physics, 2021)
In this work, porous silicon photonic crystals (PSi PhCs) covered by silver nanoparticles (AgNPs) were prepared as surface-enhanced Raman scattering (SERS) substrate to detect methylene blue (MB) at low concentrations. The limit of MB detection in water by the SERS substrate is evaluated to be 10\(^{-10}\) mol/L. The SERS signal intensities of 446 cm\(^{-1}\) and 1623 cm\(^{-1}\) peaks in SERS spectra of MB are fit in exponential functions of concentrations ranging from 10\(^{-4}\) to 10\(^{-10}\) mol/L. These results show that the AgNPs on PSi PhCs substrates could be applied in environmental sensing.